Reason for Meccan Pagan resistance against Prophet Muhammad call and their consideration of Islam as a threat - Djunaedi, Muhammad Nasir (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2025)
The objective of this present study is to comprehensively analyze the phenomenon of the resistance of Meccan pagan to the Prophet's call and their viewpoint about the call as a threat. Mecca city, the birthplace of Islam, is the place where Prophet Muhammad firstly declared his Call. However, Meccan Pagan were the first to encounter that call. Instead of receiving the call, they rejected and fought against it. This paper is regard as an endeavor to re-educate about the significance of Tawheed in field of da'wah. The objective of this paper is to provide a reminder to the relevant parties, particularly the preachers, of the significance of Tawheed and its role as a fundamental distinction between Islamic call and other. It also explores the concept of resistance as a natural phenomenon within today society as it already occurred in the Prophet era. To explain this phenomenon, this library research employed a simple comparative study as a research instrument. This study places articular emphasis on two primary aspects. Firstly, Tawheed is a pivotal clash point for this resistance and secondly this paper underwent simple comparative study about the impacts of Tawheed that were resisted by the pagan. The study used secondary source as its main source of information, given that the condition of the Prophet has been mainly documented in book of Seerah written by Moslem scholars. The research indicates that Tawheed is the factor contributing to the resistance against Prophet Muhammad's call. Thus, it is important for the Moslem preachers to always deepen their understanding about Tawheed and maintain a commitment to it considering the test given to their endeavor to propagate Islam inherently founded on Tawheed principle.